2020
DOI: 10.17261/pressacademia.2020.1365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ESG data on the financial performance of companies: a study on the airline sector

Abstract: Purpose-In recent years, financial markets around the world have faced environmental, social and governance (ESG) factors as one of the tools of investment decision-making. Therefore, ESG scores stand out as an area of increasing interest for researchers in the financial world. In the study, firstly, studies in the literature related to ESG data were examined in order to prepare the theoretical background. In the reviewed literature, there is no study conducted in the airline sector regarding the effect of ESG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…On the contrary, Ruan and Liu (2021) found in their study that ESG activities had a significant negative impact on firm performance for a sample of Shanghai and Shenzhen A-share firms in China in the 2015-2019 period. In contrast, Sisman and Cankaya (2021) examined the relationship between ESG and financial performance for 26 airline firms for the period of 2010 and 2017 and found that ESG scores have no statistically significant effect on the financial performance of airline firms. On the contrary Pulino et al (2022) confirmed the positive relationship between ESG and firm performance between 2011 and 2020 for a sample consisting of some of the largest listed companies in Italy.…”
Section: Literature Review and Related Hypothesismentioning
confidence: 99%
“…On the contrary, Ruan and Liu (2021) found in their study that ESG activities had a significant negative impact on firm performance for a sample of Shanghai and Shenzhen A-share firms in China in the 2015-2019 period. In contrast, Sisman and Cankaya (2021) examined the relationship between ESG and financial performance for 26 airline firms for the period of 2010 and 2017 and found that ESG scores have no statistically significant effect on the financial performance of airline firms. On the contrary Pulino et al (2022) confirmed the positive relationship between ESG and firm performance between 2011 and 2020 for a sample consisting of some of the largest listed companies in Italy.…”
Section: Literature Review and Related Hypothesismentioning
confidence: 99%